Enclosing the Commons in Honduras. (March 2016) - Shipley, Tyler
Abstract: We are witnessing in the 21 st century a dramatic new wave of enclosures of common resources and traditional or indigenous landholdings, as small agrarian producers across the global South are losing their land to large corporations and landowners, especially in the agribusiness and extractive industries. In the context of competing theories about land grabbing and the global commons, this article will offer a detailed empirical account of the strategies by which capital has seized land from smallholders and communities in Honduras, with emphasis on the wide variety of tactics that are used to both grab the land itself and also to maintain an aura of legality around a process that often includes at least the threat of violence.